Width-tunable pulse laser via optical injection induced gain modulation of semiconductor optical amplifiers. (1st February 2018) - Pan, Honggang; Zhang, Ailing; Tong, Zhengrong; Zhang, Yue; Song, Hongyun; Yao, Yuan
Abstract: A width-tunable pulse laser via an optical injection induced gain modulation of a semiconductor optical amplifier (SOA) is demonstrated. When the pump current of the SOA is 330 mA or 400 mA and a continuous wave is injected into the laser cavity with different powers, bright or dark pulses with different pulse widths and frequency repetition rates are obtained. The bright and dark pulses are formed by the effect of gain dispersion and cross-gain modulation of the SOA.